Model Persediaan Bahan Baku Multi Item dengan Mempertimbangkan Masa Kadaluwarsa, Unit Diskon dan Permintaanyang Tidak Konstan - Stanley Surya Jaya; Tanti Octavia; I Gede Agus Widyadana (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2012)
Many research focus on inventory problem, since inventory has significant effect to financial of a company. This research tries to develop multi items inventory models by considering expire date and unit discount with stochastic demand. Stochatic demand result in possibility of lost sales and backorder, so lost sales and backorder will be considered in the models. The models are solved using simulation and Genetic Algorithm due to complexity of the models. A numerical example and sensitivity analysis are conducted to verify the models. The sensitivity analysis shows that inventory cost and backorder cost have significant effect to ordering time.